(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the growing motivation and opportunities among young people to learn foreign languages during the period of the Third Renaissance in Uzbekistan. It examines the social, educational, and technological factors that inspire youth to develop multilingual competence in an increasingly globalized world. The paper highlights government policies, modern teaching methods, and digital learning platforms that enhance language acquisition. Special attention is given to the role of international cooperation, cultural exchange programs, and innovative educational reforms that promote linguistic diversity. The study concludes that the Third Renaissance provides a favorable environment for the younger generation to expand their linguistic skills, strengthen global communication, and contribute to the country’s intellectual and cultural development.